A Conversation with Edie Windsor - Goldberg, Suzanne B.; Gomez, Madeline M.; Chesley, Andrew (Columbia Journal of Gender and Law, 2015)
Suzanne Goldberg ISGI: It is not often that a law school gets to welcome a rock star. But in our world, Edie Windsor is a rock star. She is one of the major civil rights plaintiffs of our lifetime, whose lawsuit challenged-and triumphed over-the federal Defense of Marriage Act. Her victory in that suit has been vital to changing the landscape of marriage equality for all Americans. It is a tremendous honor, Edie, to have you here at Columbia Law School, and we welcome you.